Efficacy and Safety of Drug-Eluting Bead Bronchial Arterial Chemoembolization Plus Anlotinib in Patients With Advanced Non-small-Cell Lung Cancer - Liu, Juanfang; Zhang, Wenguang; Ren, Jianzhuang; Li, Zhen; Lu, Huibin; Sun, Zhanguo; Han, Xinwei (Frontiers in Cell and Developmental Biology, 2021)
Aim: The aim of this study is to determine the efficacy and safety of the combination therapy of drug-eluting bead bronchial arterial chemoembolization plus anlotinib oral administration in the treatment of non-small-cell lung cancer (NSCLC). Methods: Consecutive data from 51 patients with advanced NSCLC were retrospectively collected from February 2018 to August 2019. All patients underwent drug-eluting bead bronchial arterial chemoembolization (DEB-BACE) followed by anlotinib treatment. Overall survival (OS) and progression-free survival (PFS) were calculated and analyzed using the Kaplan–Meier method and log-rank test, and factors associated with OS and PFS were assessed by a Cox proportional hazards test. Treatment response at 30 days was assessed by enhanced computed tomography (CT), and then the objective response rate (ORR) and disease control rate (DCR) were calculated. Treatment-related adverse events (TRAEs) were also evaluated. Results: The median OS was 18.4 months (95% CI, 16.6–20.2 months), and the median PFS was 8.4 months (95% CI, 6.2–10.6 months). The ORR and DCR for the whole cohort were 21.6 and 100%, respectively, at 30 days after the first cycle of treatment. Most of the treatment-related adverse reactions were mild and moderate and included anorexia, hypertension, fatigue, and hand-foot syndrome. Only eight (15.7%) patients developed grade 3 TRAEs. No deaths or other serious adverse reactions occurred. Both TNM stage and brain metastasis were independent risk factors for OS and PFS. Conclusion: DEB-BACE concomitant with anlotinib has promising efficacy and tolerable toxicity in patients with advanced NSCLC.